Prevalência de distress, sintomas depressivos e estratégias de enfrentamento em pacientes recém-diagnosticados com câncer de pênis - OLIVEIRA, Fernanda Lima Britto (2019)
Introduction: Penis cancer accounts for 2% of all types of cancer that affect men in Brazil. Currently, due to its high incidence, cancer has become a public health problem. Even with all the new equipment and technological advances cancer is still full of stigmas and associated with death. Therefore, it is noted that each patient reacts subjectively to the illness / treatment and, adapting to the cancer treatment depends on the coping strategies developed during life. Objective: This study aimed to evaluate changes in the prevalence of distress, depressive symptoms and coping strategies in patients newly diagnosed with penile cancer. Methods: This research consisted of a longitudinal and prospective study composed of three validated Brazilian instruments (BDI II, Ways of Coping and Distress Thermometer) and a socioeconomic questionnaire to complement the data of this research. The individuals were evaluated in three moments (first application, three and six months after that). Result:This study found a prevalence of patients with informal professions (55%), married (73%), from country towns (82%) and 55% lived in the countryside. Regarding religion, 64% reported being Catholic. In relation educational stage, the prevalence was low educational level (55%), with a monthly income of up to 1 minimum wage (73%). There was a predominance of patients who said they were "pardos" brown (55%). A majority reported having as their main caregiver someone outside the nuclear/extensive family (46%). All of them reported an expectation of cure in relation to cancer and were receptive to the approach. In this study, the absence of distress prevailed in the three moments of application of the instruments, as well as, there was no prevalence of symptoms of depression among the patients. Regarding coping strategies, in this study, patients presented a higher prevalence of strategies that focused on the problem. Conclusions: Conclusions: This study has a clinical and epidemiological profile of patients with low income, low educational and predominance of men over 40 years of age. The emotional problems most reported by the research patients were anxiety, fear, sadness and worry. As for the physical problems, the most reported were: change of appearance, pain and alteration in the sleep cycle. As for depressive symptoms and the presence of distress, a prevalence of depressive symptoms and a high rate of distress were not observed in the study population. The coping strategies most used by the study patients were focused on the problem, with social support, positive reassessment and problem solving being the most prevalent. There was a positive association between the Beck Depression Scale and the Distress Thermometer, indicating that the more depressive symptoms reported, the higher the distress index. Regarding coping strategies, there was a positive association between social support and the Distress Thermometer result in the first evaluation time and between the escape-avoidance coping strategy and the Beck Inventory inventory scale also in the first moment of evaluation.